IMPROVING STUDENTS’ SPEAKING SKILL IN HAVING JOB INTERVIEW USING ROLE PLAY METHOD AT STMIK ASIA MALANG - Tri Wahyuni (Universitas Potensi Utama, 2019)
The demand of the working world requires students to master the English language orally and in writing become another challenge to improve students' ability in using English. For some years, English lecturers have found that the students' ability to speak English is still far from the average. Therefore, the researcher here is interested to conduct a classroom action research with the aim to improve the students’ ability to speak English by using role play method. Role play method is an alternative effort to improve speaking skill in which students are expected to be more active in using English with a more pleasant atmosphere. By applying this method, the students must act as a job seeker who is doing a job interview and an interviewer.